Identifikasi pola agroforestri yang diimplementasikan masyarakat pada laahn marjinal di lampung utara - Christine Wulandari (Institut Pertanian Bogor, 2009)
The large of marginal land in North Lampung will require careful planning towards to succeeded of the rehabilitation program. The first step that should be done is research on the identification of existing agroforestry pattern. All research results that consider to community tree preferences should be put as basis on description of objectives of next steps or further development program. Nine tree-based agroforestry patterns that applied by community at those marginal land in North Lampung namely : Clonal rubber - hedge tree, Monoculture clonal rubber, Clonal rubber- mix wood/trees, rubber forest- Phitecellobium lobatum (jengkol), Palm oil as hedge grow, Monoculture palm oil, Cacao-coffee-fruits-wood, Teak-food crops, Nephelium lappaceum (rambutan)- legum-food crops.